The Implementation of Cooperative Script Learning Model to Increase Students' Intensive Speaking Skill - Nurfia R; Abdul Haris Sunubi; Nanning (Inspiring: English Education Journal, 2020)
Intensive speaking is drills or repetitions focusing on specific phonological or grammatical points, such as minimal pairs or repetition of a series of imperative sentences, where learners are going over to practice some phonological or grammatical aspect of language. Cooperative script learning model is a learning where students work in pairs and take turns verbally summarizing the parts of the material being studied.The purpose of this research was to know the difference students’ intensive speaking skill before and after using cooperative script learning model atSMK DDI Parepare.The samples of this research were 23 students from XI TKJ (Teknik Komputer dan Jaringan) class and XI PMR (Bisnis Daring danPemasaran) class. The researcher used cluster sampling technique to decide the sample.The researcher used pre-experimental design in one group was given pre-test, treatment and post-test design.To collect the data, the researcher used tests that are pre-test and post-test. The researcher also gave observation.The result in this research was indicated that there was the improvement of the students’ intensive speaking skill. It was indicated by the students’ mean score of post-test (7) was greater than pre-test (5.5). Even, for the level significant (p) 5 % and df = 21, and the value of table is 1.721, while the value of t-test is 12.5. It means that the t-test value is greater than t-table (12.5 1.721). Thus, it can be concluded that the students’ intensive speaking skill is significant better after getting the treatment. So, the null hypothesis (H0) is rejected.